2022
DOI: 10.3389/fpls.2022.1014339
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of XTH genes in Liriodendron chinense and functional characterization of LcXTH21

Abstract: Liriodendron chinense is a relic tree species of the family Magnoliaceae with multiple uses in timber production, landscape decoration, and afforestation. L. chinense often experiences drought stress in arid areas. However, the molecular basis underlying the drought response of L. chinense remains unclear. Many studies have reported that the xyloglucan endotransglucosylase/hydrolase (XTH) family plays an important role in drought stress resistance. Hereby, to explore the drought resistance mechanism of L. chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The length of loop 2 was the key point that determined the XET or XEH activity of XTH proteins. The loop 2 of / , -B and ancestral group is shorter than that of III-A group proteins [34,43] . XET proteins speci cally recognizes xyloglucan and forms new xyloglucan chains to expand call walls [45] .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The length of loop 2 was the key point that determined the XET or XEH activity of XTH proteins. The loop 2 of / , -B and ancestral group is shorter than that of III-A group proteins [34,43] . XET proteins speci cally recognizes xyloglucan and forms new xyloglucan chains to expand call walls [45] .…”
Section: Discussionmentioning
confidence: 88%
“…Intraspecies collinearity analysis showed the chromosomal distribution of the SpuXTHs and PtrXTHs, which was determined by previous evolutionary events [34] (Figure 1A-B). The SpuXTH32 was distinctively distributed on one chromosome segment due to the incomplete genome assembly.…”
Section: Chromosome Mapping and Collinearity Analysis Of Xthmentioning
confidence: 78%
See 1 more Smart Citation
“…ABI4 mediates the balance of ABA and GA biogenesis by regulating the transcription of ABA and GA metabolic genes in opposite ways during primary seed dormancy and post-germination stages ( Shu et al., 2013 , 2016 , 2018 ). Previously, we reported that ABI4 directly regulates a set of genes involved in hypocotyl elongation, such as EXP2 ( EXPANSIN2 ), XTH5 ( XYLOGLUCAN ENDOTRANSGLUCOSYLASE/HYDROLASE 5 ), and XTH21 , which promote cell wall loosening and cell elongation ( Cho and Kende, 1997 ; Rose et al., 2002 ; Sánchez et al., 2004 ; Shin et al., 2005 ; Miedes et al., 2013 ; Xu et al., 2016 ; Wu et al., 2022 ). However, it remains unclear whether ABI4 is involved in GA signaling for the promotion of hypocotyl elongation.…”
Section: Introductionmentioning
confidence: 99%